KARAKTERISTIK KEMATANGAN BUAH MELON ‘PREMIER’ (Cucumis melo L.) BERDASARKAN SIFAT AKUSTIK - Wiyan Afriyanto Pamungkas; Nursigit Bintoro (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Determining the right time to harvest is very important to do for agricultural commodities. This is related to post-harvest handling and extending the shelf life of fruits. Determining the level of melon maturity is still done manually by tapping the surface of the fruit by hand, but this method is still subjective. This research aims to study the maturity level of the 'Premier' melon to determine the appropriate harvest time based on acoustic properties and its relationship to the physic-chemical properties of the melon using a self-made tapping device. Based on the results obtained, the acoustic properties parameters showed a strong enough relationship to the physico-chemical parameters of melons. Based on linear regression analysis, it can be seen that the best acoustic parameters in estimating and determining the right harvest time for melons are the dominant frequency (f), magnitude (M), and zero moment power (Mo). 'Premier' melons can be harvested when the dominant frequency (f) is ≤ 219.92 Hz with a magnitude (M) of ≤ 39.72 dB, and the zero moment power (Mo) value is ≤ 68.99 according to the actual harvest age in the field conducted by farmers at the harvest age of 64 DAP.